PENERAPAN METODE PEMBELAJARAN NUMBERED HEAD TOGETHER (NHT) TERHADAP HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SMP NEGERI 41 BULUKUMBA - Syamsul Bahri; Ahmad Syahid; Ratika Nengsih; Mustamin; Abdul Qahar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The aim of research is very important in achieving quality,both in the process and in educational graduates. The learning process also has the potential to contribute to the impact of low quality education. This means that learning is very dependent on the teacher's ability to carry out or package the learning process.The type of research used in this research is Classroom Action Research (PTK) which aims to improve student learning outcomes. a research activity carried out in class. Classroom action research in this study was carried out in a collaborative and participatory manner. Collaborative means that researchers work together with class VIII teachers at SMP Negeri 41 Bulukumba.The improvement in student learning outcomes in cycle I already met the criteria, out of 28 students who got very good criteria as many as 12 students or 43% while students who got good criteria were 6 students or 21%, and students who got the criteria enough as many as 6 students or by 21%. And those who got the less category were 2 students or 7%, students who got the failed category were 2 students or 7% While in cycle II there were 28 students who got very good criteria as many as 21 students or 75% while students who got good criteria as many as 5 students or 17%, and students who get sufficient criteria as many as 1 student or 4%. And those who get less criteria are 1 student or 4% so that it can be said that student learning outcomes have increased.